Retrospective Analysis of a New Antigen Assay to Detect Anti-Transglutaminase Antibodies for Diagnosis and Monitoring of Celiac Disease - Sandra Verbeke; Andrea Canals (Plasmatology, 2022)
BACKGROUND The improved diagnosis and monitoring of celiac disease (CD) requires increasingly sensitive and specific serological markers. The development of new antigens ( neo-epitope s) able to detect different sets of anti-transglutaminase antibodies requires studies to demonstrate their advantages. OBJECTIVE The goal of this study was to evaluate a new antigen for the detection of anti-tTG antibodies that combines tissue transglutaminase (tTG) and gliadin peptides. This protein complex occurs under physiological conditions in vivo at the time of deamination. PATIENTS AND METHODS In this retrospective study, serum samples collected from patients from January to December 2018 were analyzed. Results of the determinations for neo-epitope anti-tTG antibodies (manufacturer's cut-off values: negative <12 U/mL, indeterminate 12-18 U/mL; positive >18 U/mL) were recorded along with age, sex, and duodenal biopsy results. Neo-epitope assay results were correlated with clinical and laboratory data and final CD diagnoses, using the manufacturer's cut-off value and a proposed alternate cut-off value. RESULTS A total of 3820 neo-epitope anti-tTg determinations were analyzed. The percentage of values in the indeterminate zone was low (3.6%), with very few values (0.9%) at the exact manufacturer's cut-off limit (18 U/mL). This indicated a good resolution capacity for positives and negatives. The percentage of false positives was lower compared to a previous study (2013 study: 3.6%, vs current study (2018): 0.5%). A new positivity cut-off value was proposed: 20 U/mL, which increased the positive predictive value of the test. CONCLUSIONS The neo-epitope assay is a more precise tool than recombinant human transglutaminase assay for the diagnosis and monitoring of celiac patients. It has a greater ability to resolve positive and negative results (“minimum indeterminate area”). Its greater sensitivity could detect situations (presentation and/or dietary transgression) where conventional techniques show negative or weakly positive serology.